Analisis Tentang Hadits Hadits Pendidikan: Pendidik Atau Guru - Yoanda Eka Putra; Dhea Adrianda; Adilah Salsabila; Nanda Putri Maileni; Wismanto Wismanto (STIKes Ibnu Sina Ajibarang, 2024)
The importance of studying in Islam is reflected in the hadiths which emphasize that the pursuit of knowledge is an obligation for every Muslim. The research method used is textual analysis of a number of hadiths selected based on their relevance to the research topic. The analysis was conducted to identify the main messages contained in these hadiths and their implications in the context of education and the life of Muslim communities. The results showed that the hadiths on science emphasize that the search for knowledge is an obligation for every Muslim, both male and female. The hadiths of Prophet Muhammad (peace be upon him) clearly emphasize the importance of the search for knowledge as a means to understand religion, increase worship, and form good character and that knowledge is a treasure that cannot be stolen and that the search for knowledge must continue throughout life. In addition, the hadiths also affirm the high value given to scholars and scholars in Islamic society, who are respected and regarded as pillars of knowledge and wisdom. The implication of this research is the importance of developing a culture of literacy and education in Muslim societies to strengthen understanding and practice related to the importance of studying in accordance with religious teachings.